Avaliação do efeito do plasma rico em plaquetas na cicatrização de feridas cutâneas induzidas em ratos - Mendonça, Andréa Aparecida Dos Santos (2014)
The repair of injured tissues can occur by regeneration or healing, and the beginning of this healing process takes place by the activity of growth factors at the injury site stimulating chemotaxis, angiogenesis and tissue fibroplasia. The use of Platelet Rich Plasma (PRP) in tissue lesions has great therapeutic potential because it stimulates healing and regeneration, promotes neovascularization, reduce inflammation and the risk of infection, as well as to provide rapid hemostasis at the injury site. Through the induction of wounds on the dorsal region of rats, we evaluated, by histological approaches, the effect of PRP on wound healing. We used 36 albino Wistar rats in which two incisions were made on the dorsal medial region. Nothing was applied to one of the wounds, and thus, it was only filled with the blood clot (Control Group); while the other wound received PRP (Experimental Group). Animals were euthanized on day 2 (nine animals), 4 (nine animals), 7 (nine animals), and 14 (nine animals) after the surgery procedure, and tissue samples were processed for macroscopic and microscopic analyses. Results failed to show significant morphometric differences between PRP-treated and control wounds.